Probing phase transitions in a soft matter system using a single spin quantum sensor. (15th October 2019) - Kavatamane, Vinaya Kumar; Duan, Dewen; Arumugam, Sri Ranjini; Raatz, Nicole; Pezzagna, Sebastian; Meijer, Jan; Balasubramanian, Gopalakrishnan
Abstract: Phase transitions in soft matter systems reveal some of the interesting structural phenomena at the levels of individual entities constituting those systems. The relevant energy scales in soft matter systems are comparable to thermal energy ( k B T ∼ 10 −21 J). This permits one to observe interesting structural dynamics even at ambient conditions. However, at the nanoscale most experimental probes currently being used to study these systems have been either plagued by low sensitivity or are invasive at molecular scales. Nitrogen-vacancy (NV) centers in diamond is emerging as a robust quantum probe for precision metrology of physical quantities (e.g. magnetic field, electric field, temperature, and stress). Here, we demonstrate by using NV sensors to probe spin-fluctuations and temperature simultaneously to obtain information about controlled phase changes in a soft matter material as a function of temperature. The soft matter system chosen for the study is a standard liquid crystalline (LC) material which shows distinct phases close to room temperature. Individual NV centers at depths of a few nm are used as a probe to detect magnetic signals emanating from a few molecular layers of sample on the surface of the diamond. The organization and collective dynamics of LC molecules in nanoscopic volumes are discussed. Our study aims to extend the areas of application of quantum sensing using NV centers to probe the soft matter systems, particularly those exhibiting mesophases and interesting interfacial properties.